Implementation and Design of IoT Based as a File Server Storage With Raspberry Pi 3b + Using Open Media Vault: Rancang Bangun dan Implementasi Penyimpanan File Server Berbasis IoT dengan Raspberry Pi 3b+ Menggunakan Open Media Vault - Resa Rakhman; Mochamad Alfan Rosid (Academia Open, 2021)
In general, the use of IoT (Internet of Things) is still not felt, one of which is the use of IoT which can be used as a file server or storage media. Therefore, we need a storage media that is cheap, simple, efficient, does not require a large space and requires relatively fast time in designing and configuring storage media. To overcome the above problems how to build, design, create, process and utilize unused goods around so that they can become useful goods and don’t require excessive costs so as to create a service that can be used and developed in a sustainable manner. After receiving information that there is a computer that is cheap, simple, and without taking up a lot of space called the Raspberry Pi. From the background of the problem above, using the Advanced RISC Machine (ARM) architecture based on System on Chip (SoC), using Linux Open Media Vault.